Compressive creep behaviour of hot-pressed PbTe. (June 2017) - Li, C.C.; Snyder, G.J.; Dunand, D.C.
Abstract: Creep deformation is of concern in PbTe thermoelectric modules operating for years at high homologous temperatures while being subjected to internal or external stresses. The creep strain rates of hot-pressed PbTe are measured at 400 °C; a power-law is found, with a stress exponent n = 1.7 at low stresses (2–7 MPa) and n = 4.4 at high stresses (7–35 MPa). Creep rates measured at low stresses (4–6 MPa) between 350 and 500 °C provide a creep activation energy Q = 181 ± 18 kJ/mol. The creep parameters and the good hot ductility of PbTe are compared to those for cast Bi2 Te3 reported in the literature. Graphical abstract: